Phenotypic Evaluation of Genetic Diversity of Diverse Indian Mustard (Brassica Juncea L. Czern and Coss) Genotypes using Correlation and Path Analysis - Jat, Lekhraj; Rai, S. K.; Choudhary, Jeet Ram; Bawa, Vanya; Bharti, Richa; Sharma, Mridhu; Sharma, Madhavi (International Journal of Bio-resource and Stress Management, 2019)
The present investigation was undertaken at experimental field, department of plant breeding and genetics, Sher-e-Kashmir University of Agricultural Sciences and Technology, Jammu, Jammu & Kashmir state, India for phenotypic evaluation of genetic diversity in a group of Indian mustard (Brassica juncea L. Czern and Coss) genotypes. For this study we have chosen twenty Indian mustard (Brassica juncea L. Czern and Coss) genotypes with respect to thirteen different characters for assessment of genetic diversity. The analysis of variance indicated significant differences among genotypes for all the traits. High heritability coupled with high genetic advance was observed for seed yield per plant (g) followed by number of siliqua per pant, days to 50% flowering, siliqua length (cm). Results revealed that in some genotypes seed yield had high heritability so it would show very good response on selection, so selection of such promising genotypes would be rewarded. The overall mean performance of genotypes was comparatively higher for days to 50% flowering, days to maturity, plant height (cm), primary branches plant-1, secondary branches per plant, number of siliqua plant-1, siliqua length (cm), number of seeds silique-1, test weight (g), percent oil content,seed yield plant-1 (g). This study further can be useful for selection of desirable genotypes of Indian Mustard to fulfil the various breeding objectives.